Potato Cyst Nematodes – The Policy Paralysis (Indian Journal of Nematology, 2024)
PCN was intercepted in north India in the farm area of ICAR-Central Potato Research Institute (CPRI), Himachal Pradesh. CPRI being a nodal institution for the development of potato varieties/hybrids, a lot of germplasm and seed material exchange takes place between the institution and other Central/State Government agencies mandated to work on potato in the country. The basic seed produced at the farms of CPRI is multiplied at different Govt. Potato Seed Multiplication Farms (GPSMFs) of States/UTs, Departments of Agriculture Himachal Pradesh, Uttarakhand, and Jammu & Kashmir for further distribution to farmers in these andother states of the country. Considering the present scenario on the distribution of PCN in the three hilly states/UTs of North India,some general inferences can be drawn. (i) High populations of PCN were recorded at GPSMFs; this may be due to the continuouscropping of potato in these farms. Circumstantial evidence reveals the nematodes must have been introduced long ago, but due to nonspecific above-ground symptoms and lack of awareness, they could not be detected earlier. (ii) GPSMFs may be contributing towards the dissemination of PCNs to farmers’ fields, but the low populations in PCN-conducive areas could be due to discontinuous cultivation of potato crop. (iii) Populations of PCN at lower altitudes (